REPRESENTASI IDENTITAS SANTRI (Analisis Semiotika Model John Fiske Dalam Film Cahaya Cinta Pesantren) - Hagi Julio Salas; Tina Kartika (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2020)
The film is included in the mass communication media that are considered capable of being an effective media to persuade and persuade a broad audience. The film influences audiences through signs that appear in shows like in the Film Cahaya Cinta Pesantren. This research was conducted to determine the signs that represent identity in the film Cahaya Cinta Pesantren. This type of research is descriptive qualitative by using John Fiske's semiotic analysis model. The results of this study are the representations of santri's representations composed by John Fiske's semiotic code, namely appearance, expression, camera, setting, and action. In addition, this film also contained subcultural ideology, namely students are figures who come out of the dominant culture with daily activities that are more concerned with the afterlife.